Association of body mass index and gastroesophageal reflux disease and its complications - Singh, Sarmukh Singh A/L Charanjit (2018)
Introduction: Obesity is a fast-emerging epidemic in the Asia-Pacific region especially in Malaysia. According to National Health and Morbidity Survey of 2015, obesity in Malaysians make up 17.7 per cent of the population while those who are categorised as overweight make up 30 per cent..The landscape of gut diseases in Asia has been drastically changed by obesity, especially the gastroesophageal reflux disease (GERD) and its complication such as hiatus hernia, reflux esophagitis and Barrett's esophagus. The objectives of this study are to determine the association between GERDs complications such as hiatus hernia, reflux esophagitis and Barrett's esophagus with body mass index via esophagogastroduodenoscopy (OGDS) in Hospital Universiti Sains Malaysia (HUSM). Methods: GERD patients with GerdQ questionaire scoring system who had underwent OGDS in Hospital Universiti Sains Malaysia from January 2014 to Mei 2017 were reviewed retrospectively. The patients were divided into 2 groups according to their body mass index (BMI) based on WHO (ASIAN population classification) : 1) Normal BMI group with BMI less than 22.9 kg / (m2) (54 patients) and 2) Obese group with the BMI more than 23 kg / (m2) (73 paients). The clinical factors (age, gender, ethinicity, weight, height, BMI and GerdQ questionaire scoring) and OGDS findings (hiatus hernia, reflux esophagitis and Barrett's esophagus) were analyzed. We used a gastroentrologist to be the interobserver to analyse the OGDS films.He graded the findings based to it severity. Hiatus hernia by using Hill's Grading, reflux esophagitis according to Los Angeles classification and Barrett's esophagus according to Prague Classififcation (C and M). Results: A total sample of 127 patients were included in this study where male population predominantly conquered with 57.48% compared to female population which is 42.52% . The mean age of the samples were 43.91 years old. Obesity as in BMI > 30 kg/m2 were statistically significant association (p = 0.028) with Hiatus hernia based on Hill's Grading and statistically significant association (p = 0.015) with reflux esophagitis based on LA classification. However, obesity was statistically insignificant association (p = 0.704) with Barrett's esophagus histologically. Obese patient also showed statistically insignificant association with Barrett's esophagus endoscopically based on Prague classification of Circumferential of metaplasia (C) (p = 0.660) and Maximum extend of metaplasia (M) (p = 0.524). The risk prediction shows statistically significant association (p = 0.002) between Body Mass Index (BMI) with reflux esophagitis based (LA Classification). Those in obese group have 3.6 times higher Odds to get reflux esophagitis symptoms compared to those in normal BMI group. Conclusion: Obese patient has association with hiatus hernia and reflux esophagitis ,but not for the Barrett's esophagus. The risk prediction association between Body Mass Index (BMI) is with Reflux Esophagitis based (LA Classification) in obese group have 3.6 times symptoms compared to those in normal BMI group. In obese patient with severe and persistent GERD symptoms such as regurgitation and heartburn despite on medical treatment (Proton pump inhibitor) should undergo bariatric surgical correction. We suggest that, Laparoscopic Roux En Y Gastric bypass procedure have shown to be more effective procedure for alleviating the symptoms of GERD as it plays a role in significant weight loss compare with laparoscopic sleeve gastrectomy patient.